Implikasi Tradisi Masyarakat yang Mempengaruhi Kesakralan Pemandian Putri Hijau di Deli Tua - Ningsih, Rindia; Nugraha, Adika; Sumantri, Pulung (Polyscopia, 2025)
This study examines the influence of community traditions on the sacredness of Putri Hijau Bath in Deli Tua Village. The research objectives are to: (1) explore the origins and historical development of Putri Hijau Bath; (2) analyze how the local community perceives the site as sacred; (3) examine the religious values and traditions associated with the bath and their role in cultural preservation; and (4) assess the impact of modernization and socio-cultural changes on the perception and practice of sacredness in Deli Tua Village. The study employs a qualitative historical research method, collecting data through triangulation techniques, including interviews, observations, literature analysis, and documentation. The data is obtained using purposive sampling and analyzed through qualitative descriptive analysis. The findings highlight four key aspects: (1) the historical evolution of Putri Hijau Bath; (2) community perceptions of its sacredness; (3) the importance of religious values and traditions in maintaining cultural heritage among the younger generation; and (4) the role of modernization and socio-cultural transformations in shaping contemporary interpretations of the bath’s sacredness. The study underscores the need for cultural preservation amid changing societal norms and beliefs.